Spectrum Efficiency of Jointing Adaptive Modulation Coding and Truncated ARQ With QoS Constraints - Jiao, Wanguo; Ding, Haofan; Wu, Haiqing; Yu, Gang (IEEE access, 2018)
Spectrum efficiency (SE) and QoS guarantee are two critical issues in wireless communication systems. The truncated ARQ and the adaptive modulation and coding (AMC) are often used to improve the SE and transmission reliability in wireless communications. In this paper, we study the SE and QoS performance of a system with a cross-layer combining of the truncated ARQ with the AMC. First, we analyze the performance of current combinations of the ARQ and the AMC. The analysis results indicate that the current combination is too "ineffectiveness" or "conservative." Then, based on the analysis, we design a new rule for the AMC, which is used to adaptively choose transmission mode. Through analyzing the AMC and the combination algorithm using the proposed rule, both the SE and the packet dropped probability of the system are improved. Furthermore, the analysis result also point outs the suitable scenario of each algorithm. Simulation results verify the analysis result and demonstrate that the proposed algorithm can achieve higher SE while the QoS requirement is guaranteed. At last, to further improve the SE of the system, we propose an algorithm jointing power control and the combination of the ARQ with the AMC under the QoS constraint.